1999
DOI: 10.1002/hep.510290614
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of severe subfulminant hepatitis in heart-transplanted patients after nosocomial transmission of a mutant hepatitis B virus

Abstract: Fulminant and severe viral hepatitis are frequently associated with mutant hepatitis B virus (HBV) strains. In this study, the genetic background of a viral strain causing severe subfulminant outcome in heart-transplanted patients was studied and compared with viral hepatitis B strains that were not linked to severe liver disease in the same setting. A total of 46 patients infected nosocomially with HBV genotype A were studied. Five different viral strains were detected, infecting 3, 9, 5, 24, and 5 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…Point mutations within the CD 4 + T-cell epitope aa 48-69 [117] were described in severe liver diseases from patients from South-East-Asia [126,127], from immunocompromized patients [132] and from hepatoma tissues [16] [133]. These mutations were found after antiHBe seroconversion in chronic active hepatitis and in immunocompromized patients.…”
Section: Mutations Of the Core-regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Point mutations within the CD 4 + T-cell epitope aa 48-69 [117] were described in severe liver diseases from patients from South-East-Asia [126,127], from immunocompromized patients [132] and from hepatoma tissues [16] [133]. These mutations were found after antiHBe seroconversion in chronic active hepatitis and in immunocompromized patients.…”
Section: Mutations Of the Core-regionmentioning
confidence: 99%
“…Point mutations within the highly conserved domain E of the X-gene (Ile-127 to Thr, Lys-130 to Met, Val-131 to Ile) recently were described in Japanese patients with fulminant and chronic hepatitis [176] and in immunocompromized patients with fulminant hepatitis [132]. It was shown that these mutations affecting the crucial domain for transactivation suppress the transcription of both precore and core mRNA [177].…”
Section: Nuclear Pathwaysmentioning
confidence: 99%
“…26 To detect the variability of the viral genome at codon 28 and 29 of the precore region and at nucleotides 1,762 and 1,764 of the core promoter, a research LiPA was used with specific probes as described in detail previously. [27][28][29] To determine genotypic resistance and detect polymerase gene variability at codon 528 in the B domain of the reverse transcriptase, and at codons 552 and 555 of the C domain, a research LiPA was used as described previously in detail. 21 As the HBV polymerase gene has a different nucleotide length depending on genotypes, genotype A corresponding to the longest polymerase gene sequence was used as a reference for amino acid numbering.…”
Section: Determination Of Viral Genotypes and Detection Of Precore Anmentioning
confidence: 99%
“…A common phenotype for these variants is decreased synthesis of precore mRNA resulting in decreased production of HBeAg and enhanced virus replication (24,56). These mutations are almost always found together and have been identified in HBV variants derived from patients with fulminant progression, chronic active infection, and primary liver cancer (23,32,58). At present, despite some reported evidence, there is no final consensus as to whether these core promoter variants are indeed more virulent.…”
mentioning
confidence: 99%